AutoCaSc: Prioritizing candidate genes for neurodevelopmental disorders. Issue 12 (14th September 2022) - Lieberwirth, Johann Kaspar; Büttner, Benjamin; Klöckner, Chiara; Platzer, Konrad; Popp, Bernt; Abou Jamra, Rami
Abstract: Routine exome sequencing (ES) in individuals with neurodevelopmental disorders (NDD) remains inconclusive in >50% of the cases. Research analysis of unsolved cases can identify novel candidate genes but is time‐consuming, subjective, and hard to compare between labs. The field, therefore, requires automated and standardized assessment methods to prioritize candidates for matchmaking. We developed AutoCaSc (https://autocasc.uni-leipzig.de ) based on our candidate scoring scheme. We validated our approach using synthetic trios and real in‐house trio ES data. AutoCaSc consistently (94.5% of all cases) scored the relevant variants in valid novel NDD genes in the top three ranks. In 93 real trio exomes, AutoCaSc identified most (97.5%) previously manually scored variants while evaluating additional high‐scoring variants missed in manual evaluation. It identified candidate variants in previously undescribed NDD candidate genes ( CNTN2, DLGAP1, SMURF1, NRXN3, and  PRICKLE1 ). AutoCaSc enables anybody to quickly screen a variant for its plausibility in NDD. After contributing >40 descriptions of NDD‐associated genes, we provide usage recommendations based on our extensive experience. Our implementation is capable of pipeline integration and therefore allows the screening of large cohorts for candidate genes. AutoCaSc empowers even small labs to a standardized matchmaking collaboration and to contribute to the ongoing identification of novel NDD entities.